2017
DOI: 10.1128/mbio.02329-16
|View full text |Cite
|
Sign up to set email alerts
|

Role of Eosinophils and Tumor Necrosis Factor Alpha in Interleukin-25-Mediated Protection from Amebic Colitis

Abstract: The parasite Entamoeba histolytica is a cause of diarrhea in infants in low-income countries. Previously, it was shown that tumor necrosis factor alpha (TNF-α) production was associated with increased risk of E. histolytica diarrhea in children. Interleukin-25 (IL-25) is a cytokine that is produced by intestinal epithelial cells that has a role in maintenance of gut barrier function and inhibition of TNF-α production. IL-25 expression was decreased in humans and in the mouse model of amebic colitis. Repletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Recently, we reported that IL-25 mediated mucosal barrier function plays an important role in the protection from intestinal E . histolytica infection [ 24 ]. Also, it is known that secretion of IL-25 could be reduced by antibiotic induced dysbiosis [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that IL-25 mediated mucosal barrier function plays an important role in the protection from intestinal E . histolytica infection [ 24 ]. Also, it is known that secretion of IL-25 could be reduced by antibiotic induced dysbiosis [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, where immunization by a unique helminth protein (P28GST) alters the susceptibility of mice to colitis in a preventive manner, we previously demonstrated that such anti-inflammatory effects encompass the contribution of mucosal eosinophils, acting as T-helper-type (Th2) response inducers [7]. In addition to systemic and local induction of IL-13 and IL-5, a possible role of IL-25 can be hypothesized, as it has recently been shown in protection from amoebic colitis, acting via eosinophils and suppression of TNF-α through a new pathway of innate mucosal immune response [39].…”
Section: Discussionmentioning
confidence: 99%
“…139). For host defence responses to non-classical microbial targets, eosinophil-derived IL-25 helps to mediate protection from protozoan parasite-elicited amoebic colitis 140 , and eosinophils, as sources of IL-23 and IL-17, are immunomodulatory in fungal aspergillosis 141 . In response to systemic IL-33 administration, ILC2-derived IL-5 and the associated eosinophil recruitment have both been shown to promote increased pulmonary artery hypertrophy, which is a previously unrecognized role for eosinophils 142 .…”
Section: Eosinophils In Other Host Responsesmentioning
confidence: 99%